2016
DOI: 10.1021/acs.jpcc.6b06347
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Vanadium Precursor for VO2 Thin-Film Growth in the Atomic Layer Deposition Process by Multiscale Simulations

Abstract: To develop an effective vanadium precursor for the atomic layer deposition (ALD) of VO 2 thin films on glass, ALD reactions were investigated via a multiscale approach combining density functional theory (DFT) and an off-lattice kinetic Monte Carlo (KMC) model. Tris(dimethylamino) cyclopentadienyl vanadium (CpV(NMe 2 ) 3 ) was designed as a novel precursor and compared with tetrakis(ethylmethylamino) vanadium (TEMAV). DFT was applied to predict the thermal stability and adsorption energy of precursors and ALD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Alkylamide compounds Vanadium (IV) amide complexes are volatile, reactive, produce noncorrosive by-products, and leave marginal impurities in the films, [58]. Alkylamide compounds with higher molec-ular weight decompose at higher temperatures due to the steric hindrance, [59,60]. Ethylamide compound have e.g.…”
Section: Alkoxide Compoundsmentioning
confidence: 99%
“…Alkylamide compounds Vanadium (IV) amide complexes are volatile, reactive, produce noncorrosive by-products, and leave marginal impurities in the films, [58]. Alkylamide compounds with higher molec-ular weight decompose at higher temperatures due to the steric hindrance, [59,60]. Ethylamide compound have e.g.…”
Section: Alkoxide Compoundsmentioning
confidence: 99%
“…Several studies have been systematically reported using ALD technique to deposit VO 2 thin films. , However, to our knowledge, doped VO 2 films by ALD process have not been reported yet. To deposit Mo-doped VO 2 film by ALD nanolamination method, one prerequisite is that the reactor temperature should meet the requirement of the deposition temperature for both VO 2 and MoO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Common methods for depositing VO 2 and doped VO 2 films are reactive sputtering, 11) chemical vapor deposition (CVD), 12) pulsed laser deposition (PLD), 13) and atomic layer deposition (ALD). 14,15) Among them, ALD is a state-of-the-art deposition method for the fabrication of dense metal oxide films with ultrasmooth surfaces and pin-hole-free textures. 16) However, the ALD method is seldom used to deposit porous films.…”
Section: Introductionmentioning
confidence: 99%